Design Get up E-commerce based Marketplace Sale Chips Web Based In Padang City - Dewi, Ika Parma; Firza, Fahira Utami; Sriwahyuni, Titi; Hendriyani, Yeka (Politeknik Ganesha Medan, 2023)
This web-based e-commerce is designed to help chip manufacturers sell their products and make it easier for consumers to get chips through internet technology. The web design method uses the prototype method starting with conducting needs analysis, interface design and programming and utilizing PHP programming as a programming language, MySQL as a database, XAMPP as a server and the Codeigniter framework version 4. Chips are a food that is much loved by people of all ages. This has caused many people to start a business selling chips, ranging from home industries to larger production. However, not a few of the chip entrepreneurs have difficulty managing the sale of their chip products to chip consumers such as students, workers and the general public. This is also a result of the outbreak of the Covid-19 virus which is experienced globally, including Indonesia, making it difficult for chip manufacturers to market their products and manage their sales. On the chip consumer side, they also find it difficult to get chips amidst pandemic conditions and busy activity. The difficulties of chip manufacturers and chip consumers can be overcome by developing a system in the form of e-commerce that can be accessed by chip consumers by adapting internet technology. The results of this design produce a web-based e-commerce selling chips by taking a case study in the chips business in Padang City, West Sumatra Province.